Increased sensitivity of etoposide-treated breast cancer cells with an ATM inhibitor - Arun R. K. Kumar; Crystal Sara Shaji; Aswathi Rajagopalan; Sombodhi Bhattacharya; Wilner Martínez-López; Radha Saraswathy (PLoS ONE, 2026)
Breast cancer remains the leading cause of cancer-related deaths in women. Therefore, developing targeted combination therapies that improve overall survival in breast cancer patients continues to pose a major clinical challenge. Etoposide (ETO), a topoisomerase II inhibitor that induces transient double-strand breaks by blocking the cleavable complex, is currently used in high doses to treat radioresistant or metastatic breast cancers. To enhance the effectiveness of radiation and chemotherapy, targeting molecular mechanisms involved in DNA repair of induced DNA lesions could selectively increase tumor cell death. Since the effects of ETO are primarily seen during the S/G2 phases of the cell cycle, its efficacy could potentially be enhanced by using an inhibitor of a DNA repair gene involved in homologous recombination, which is mainly active during these phases. In this context, synthetic lethality refers to the concept that inhibiting or mutating two or more genes simultaneously leads to greater cell death than altering them individually. The FDA approval of Olaparib, a specific PARP inhibitor for BRCA-mutated breast cancer patients, has motivated researchers to explore other synthetic lethal interactions that could increase DNA damage accumulation, leading to cancer cell death. We demonstrate that successive treatment of breast cancer cells with specific inhibitors of ATM kinase and topoisomerase II in vitro can induce increased apoptosis. ATM is an apical kinase that recognizes DNA double-strand breaks and activates the homologous recombination repair pathway, either directly or through cell cycle checkpoint control. Topoisomerase II poisons generate enzyme-mediated DNA damage, leading to permanent double-strand breaks. Cytokinesis-block micronucleus assay was performed to assess the increase in DNA damage during combination treatment with inhibitors. Additionally, cell viability tests and fluorescent staining assay were conducted to evaluate the extent of cell death. We found that targeting ETO-treated breast cancer cells with an ATM kinase inhibitor, KU-55933 (KU) induced higher chromosomal damage/aberrations, as evaluated by the cytokinesis-block micronucleus assay. The ATM kinase inhibitor also significantly reduced the viability of ETO-treated breast cancer cells.